Genesis of Quality Measurements to Improve the Care Delivered to Patients With Brain Metastases. Issue 3 (March 2021) - Silvestre, Julio; Gosse, Tracey; Read, Paul; Gentzler, Ryan; Purow, Benjamin; Asthagiri, Ashok; Gaughan, Elizabeth; Dillon, Patrick M.; Larner, James M.; Anderson, Roger T.; Sheehan, Jason P.; Fadul, Camilo E.
Abstract : PURPOSE: High-value and high-quality health care requires outcome measurements to inform treatment decisions, but, to our knowledge, no standardized measurements exist to evaluate brain metastases (BMs) care. We propose a set of measurements and report on their implementation in the care of patients with BMs. METHODS: On the basis of a stakeholders' needs assessment and review of the literature, we identified outcome and process measurements to assess the care of patients with BMs according to treatment modality. Retrospectively, we applied these indicators of care to all patients diagnosed and treated at our institution over 2 years. RESULTS: We ascertained 5 outcome and 6 process measurements of relevance in the care of BMs. When applied to 209 patients (89.7%) who received cancer treatment, 77% were alive > 90 days after diagnosis. The proportion alive at 90 days after surgery, whole-brain radiation therapy (WBRT), and stereotactic radiosurgery (SRS) was 82%, 59%, and 81%, respectively. Other performance measurements included 30-day postoperative readmission rate (6%), SRS within 30 days of surgery (79%), use of memantine with WBRT (41%), advance directives within 6 months of diagnosis (53%), and palliative care consultation for patients with poor prognosis or receiving WBRT (45%). Measurements for the 24 patients (10.3%) receiving best supportive care were advance directives documentation (67%) and referral to palliative or hospice care (83%). CONCLUSION: We propose a set of measurements to apprise quality improvement efforts, inform treatment decision-making, and to use in evaluation of the performance of interdisciplinary BMs programs. Their refinement can potentially enhance the quality and value of care delivered to patients with BMs.